2018
DOI: 10.1093/infdis/jiy152
|View full text |Cite
|
Sign up to set email alerts
|

Fusion Inhibitory Lipopeptides Engineered for Prophylaxis of Nipah Virus in Primates

Abstract: The experiments provide a proof of concept for the use of antifusion lipopeptides for prophylaxis of lethal NiV. These results advance the goal of rational development of potent lipopeptide inhibitors with desirable pharmacokinetic and biodistribution properties and a safe effective delivery method to target NiV and other pathogenic viruses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(48 citation statements)
references
References 46 publications
1
47
0
Order By: Relevance
“…Recently, numerous reports have shown that the lipidation strategy can effectively improve the antiviral activity of fusion inhibitory peptides, such as the ant-HIV-1 peptide LP-19, 18 and the anti-Nipah virus lipopeptides. 19 In order to improve the inhibitory activity of EK1, cholesterol (Chol) and palmitic acid (Palm) were covalently attached to the Cterminus of EK1 sequence under the help of a flexible polyethylene glycol (PEG) spacer, and the corresponding lipopeptides EK1C and EK1P were constructed, respectively ( Fig. 4a).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, numerous reports have shown that the lipidation strategy can effectively improve the antiviral activity of fusion inhibitory peptides, such as the ant-HIV-1 peptide LP-19, 18 and the anti-Nipah virus lipopeptides. 19 In order to improve the inhibitory activity of EK1, cholesterol (Chol) and palmitic acid (Palm) were covalently attached to the Cterminus of EK1 sequence under the help of a flexible polyethylene glycol (PEG) spacer, and the corresponding lipopeptides EK1C and EK1P were constructed, respectively ( Fig. 4a).…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, at the end of 2019, the outbreak of Wuhan pneumonia with an unknown etiological agent, the first Disease X following WHO's announcement was reported to WHO. Shortly thereafter, a novel coronavirus, SARS-CoV-2 (also known as 2019-nCoV or HCoV- 19), was identified to be the etiology of the Wuhan pneumonia, i.e., COVID-19 as designated by WHO.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical examinations were performed on 0, 1, 3,5,8,15,19,23,28,35,42,50,63, and 92 dpi. On examination days, clinical parameters such as bodyweight, respiration rate, and oxygen saturation (SPO 2 ), as well as a blood sample and oral and nasal swabs, were collected.…”
Section: Methodsmentioning
confidence: 99%
“…Favipiravir protected hamsters from lethal Nipah virus Malaysia infection when treatment was administered orally or subcutaneously immediately after inoculation and continued for 13 days (4). Fusion inhibitory lipopeptides were shown to reduce mortality by 33% in the African green monkey (AGM) model of Nipah virus disease when administered daily from 1 day before until 5 days after inoculation with Nipah virus Malaysia (5). To date, only monoclonal antibody m102.4 treatment has shown efficacy in nonhuman primates when administered therapeutically (6,7).…”
Section: Introductionmentioning
confidence: 99%
“…Its mortality varies as per the outbreak and till date there is no inhibitors of NiV due to the constraints of being BSL4 pathogen. In literature few studies have been done regarding the development of inhibitors (Dawes et al, 2018;Mathieu et al, 2018). In the current study, we identified the DEGs among two different studies and tried to find out the common and different genes, which are up and down regulated.…”
Section: Discussionmentioning
confidence: 99%